2000
DOI: 10.1161/01.hyp.35.3.732
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Big Endothelin-1–Induced Diuresis and Natriuresis

Abstract: Endothelin-1 (ET-1) at high concentrations has marked antidiuretic and antinatriuretic activities, whereas its precursor, big endothelin-1 (big ET-1), has surprisingly potent diuretic and natriuretic actions. The mechanisms underlying the excretory effects of big ET-1 have not been fully elucidated. To explore these mechanisms, we examined the effects of a highly selective ET(B) antagonist (A-192621.1), a calcium channel blocker (verapamil), a nitric oxide synthase inhibitor (N-nitro-L-arginine methyl ester [L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 56 publications
4
42
1
Order By: Relevance
“…This observation is further supported by our laboratory's previous findings that ET B receptor is preferably expressed in the outer and inner medulla, mainly in the vasa recta, thick ascending limb of Henles' loop, and collecting duct (11). Moreover, our finding that ET B blockade worsened the oliguria characterizing pneumoperitoneum supports the role of tubular ET B receptors in mediating the diuretic effect of ET-1 under physiological conditions (11,18,25).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This observation is further supported by our laboratory's previous findings that ET B receptor is preferably expressed in the outer and inner medulla, mainly in the vasa recta, thick ascending limb of Henles' loop, and collecting duct (11). Moreover, our finding that ET B blockade worsened the oliguria characterizing pneumoperitoneum supports the role of tubular ET B receptors in mediating the diuretic effect of ET-1 under physiological conditions (11,18,25).…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, several studies have demonstrated that medullary NO plays a pivotal role in the regulation of renal medullary hemodynamics and excretory function (27,28,30). Previously, our laboratory (14,18) and others (48) have shown that the renal vasodilatory actions of ET B , as well as its stimulatory effects on water and sodium excretion, are mediated through generation of NO. Similarly, Mattson et al (32) have demonstrated that chronic intravenous administration of the NO synthase inhibitor N G -nitro-L-arginine methyl ester (L-NAME) selectively decreases renal medullary blood flow, causes sodium and water retention, and leads to hypertension.…”
mentioning
confidence: 95%
“…Inner medullary ET-1 is well characterized natriuretic peptide that stimulates compounds such as nitric oxide and cGMP (55,61). Similarly, ET-1 potently inhibits sodium transport through the epithelial sodium channel in collecting duct cells (34,36). Consequently, aldosterone induction of edn1 may represent an important negative feedback loop on aldosterone-stimulated sodium reabsorption in the collecting duct.…”
Section: Discussionmentioning
confidence: 99%
“…These same processes are also influenced by aldosterone. However, renal ET-1 is a well documented natriuretic peptide that directly blocks sodium transport in the tubule collecting duct (28,(33)(34)(35)(36)(37). The physiological importance of collecting duct ET-1 is emphasized by the fact that collecting duct cell-specific edn1 knock-out mice exhibit saltsensitive hypertension (31).…”
mentioning
confidence: 99%
“…This response, which resembles the effect of mannitol, is mediated at least in part by an increase in plasma volume and the release of natriuretic peptides (14 -16). Natriuresis and diuresis may also be related to dye-induced endothelin release (14), mediated through ET B endothelin receptors (17). All of these factors, in addition to the substantial osmotic load provided by hyperosmolar radiocontrast agents, enhance solute delivery to the distal nephron and lead to increased oxygen consumption caused by enhanced tubular sodium reabsorption.…”
Section: Radiocontrast Agents Increase Renal Oxygen Demandmentioning
confidence: 99%